2019
DOI: 10.1007/s10067-019-04747-3
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported involvement of the eighth cranial nerve in giant cell arteritis

Abstract: Introduction The frequency of eighth nerve lesions in patients with giant cell arteritis (GCA) has rarely been examined. However, sudden onset deafness has been recorded as a presenting feature of GCA on several occasions. This study sought to establish how common this and other symptoms of eighth nerve involvement are in a large retrospective survey. Methods We contacted 170 patients with GCA and 250 matched PMR patients, inviting them to participate in a questionnaire survey of symptoms of eighth nerve dysfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…13 Recovery from vertiginous symptoms was not as pronounced as recovery of hearing loss. 11 The mechanism of deafness is not entirely understood but may involve arterial wall inflammation of the posterior circulation or terminal cochleovestibular vasculature. 14 Multiple theories have been suggested regarding the exact mechanism, including vascular occlusion, immunological mechanisms and viral infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Recovery from vertiginous symptoms was not as pronounced as recovery of hearing loss. 11 The mechanism of deafness is not entirely understood but may involve arterial wall inflammation of the posterior circulation or terminal cochleovestibular vasculature. 14 Multiple theories have been suggested regarding the exact mechanism, including vascular occlusion, immunological mechanisms and viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement of hearing post‐steroids occurs in 56% of patients, 11 with early administration of steroids important in the recovery of SNHL 13 . Recovery from vertiginous symptoms was not as pronounced as recovery of hearing loss 11 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although hearing loss and elevations in the erythrocyte sedimentation rate and C-reactive protein level are consistent with this condition, the patient is young for the development of temporal arteritis; the mean age at onset is 72 years. 1,2 In addition, there was no jaw claudication or vision loss, and the lack of a response to glucocorticoids and the normal retinal examination make this possibility unlikely. 3 The history of shingles suggests the possibility of a recurrence of herpes zoster oticus.…”
Section: Temporal Painmentioning
confidence: 99%
“…Previous studies have demonstrated that otologic involvement is rather common in GCA patients, with an incidence ranging from 25% [4] to 53% [5]. Sensorineural hearing loss is predominant and usually concomitant with other ischemic symptoms on the ipsilateral side, including ocular involvement, eye pain, and tenderness of the temporal artery [4,6].…”
Section: Introductionmentioning
confidence: 99%